Poverty Alleviation Through Social Capital in Coastal Areas: Pariaman Coastal Case - Kamarni, Neng; Anshori, Muslich; Sukmana, Raditya (Journal of Innovation in Business and Economics, 2019)
This study aimes to provide an overview of the importance of social capital in poverty alleviation in Pariaman coastal area. The research was a survey research conducted in Padang Pariaman District, sample was conducted purposively sampling with 100 fishermen households as a sample. The result revelead that institution and culture variables get good categories while trust and participation variables are categorized as poor. The institution is one of four variables which has a significant correlation with welfare while the others are not significant. Trust and participation variables not have a significant correlation because they get poor category, but the interesting case even though the culture variable which gets a positive category but does not correlate significantly with the welfare. Although only institution variable which has a significant correlation with welfare, in general social capital has a positive impact on poverty alleviation in Pariaman Distric.